Children in the Malaysian entertainment industry and their right to education / Dina Imam Supaat ... [et al.] - Imam Supaat, Dina; Che Amani, Nurfadhilah; Osman, Suraiya; Yaakob, Adzidah; Abdul Rahman Shah, Hendun (2014)
Regardless of the reasons and factors that encourage or force children to work, due to their age, physical development and vulnerability, unsuitable work and its condition can have adverse affect on children. There is concern that their right to education can be affected as their working hours operates within the same time children go to school. This study intends to look at the working condition of children in the show business in Malaysia and how has their right to education is affected and then being realised. Its objective is to describe and discuss the environment of the entertainment industry where children are working in the country generally, and to identify the basic legal principles governing minors and their involvement in the industry. The next focus is to identify significant problems in the protection of minors rights to education especially issues pertaining to their welfare. Using qualitative study based on library research, this study shows that law and policy reform; and legal enforcement is needed to fully protect children from any risk and harm. It also show that parents’ role as a guardian of children’s right is sometimes questionable. This study also indicates that in ensuring children’s enjoyment of their basic right to education, the correct way forward is to adopt the rights based approach.